2023
DOI: 10.3389/fimmu.2022.1023553
|View full text |Cite
|
Sign up to set email alerts
|

Alpha-1 antitrypsin limits neutrophil extracellular trap disruption of airway epithelial barrier function

Abstract: Neutrophil extracellular traps contribute to lung injury in cystic fibrosis and asthma, but the mechanisms are poorly understood. We sought to understand the impact of human NETs on barrier function in primary human bronchial epithelial and a human airway epithelial cell line. We demonstrate that NETs disrupt airway epithelial barrier function by decreasing transepithelial electrical resistance and increasing paracellular flux, partially by NET-induced airway cell apoptosis. NETs selectively impact the express… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
11
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(11 citation statements)
references
References 104 publications
0
11
0
Order By: Relevance
“…3B). To model the inhibition of serine proteases in lung lining fluids, we also included the most prevalent NE inhibitor, AAT (α 1 -AT) (31)(32)(33)(34). The presence of 1 μM AAT inhibited the NE activity by 58 ± 21% in DHNEs [both groups contain DNA (0.2 mg ml −1 )] and by 74 ± 8% in NETs (Fig.…”
Section: Resultsmentioning
confidence: 99%
“…3B). To model the inhibition of serine proteases in lung lining fluids, we also included the most prevalent NE inhibitor, AAT (α 1 -AT) (31)(32)(33)(34). The presence of 1 μM AAT inhibited the NE activity by 58 ± 21% in DHNEs [both groups contain DNA (0.2 mg ml −1 )] and by 74 ± 8% in NETs (Fig.…”
Section: Resultsmentioning
confidence: 99%
“…We have previously reported that HBE exposed to NETs have a significant decrease in barrier function, as measured by the TEER of epithelial monolayers [ 13 ]. However, it was unknown if NET components would consistently demonstrate similar associations across multiple donors.…”
Section: Resultsmentioning
confidence: 99%
“…Excess NE is associated with worse structural lung disease in CF and COPD [ 12 ]. We have demonstrated that NET serine proteases cause significant bystander tissue damage, as exposing normal human bronchial epithelial cells (HBE) to NETs led to a breakdown in epithelial barrier integrity, including decreases in transepithelial electrical resistance (TEER) [ 13 ]. We have shown that NET exposure also drives inflammation through NE by activating the IL-1 pathway in the epithelium, leading to the secretion of TNF-α and IL-8 [ 14 ].…”
Section: Introductionmentioning
confidence: 99%
“…Elevated NETs are present in many lung diseases including Cystic Fibrosis (CF), non-CF bronchiectasis, asthma and COPD (27)(28)(29)(30). We and others have demonstrated that NETs can disrupt barrier function of the epithelium and endothelium, a key mechanism of NET-induced pathogenesis in the lung (10,31). NETs are complex structures with over 100 proteins, many of which are immunomodulatory, so defining NET concentrations is challenging.…”
Section: Discussionmentioning
confidence: 99%
“…Likewise, the degree to which these components correlate with NET-induced lung tissue injury have not been investigated. We previously reported that exposing primary normal human bronchial epithelial cells (HBE) to NETs led to a breakdown in epithelial barrier integrity including decreases in transepithelial electrical resistance (TEER) (10). NET exposure also drove epithelial secretion of select inflammatory cytokines, TNF- α and IL-8, via activation of the IL-1 pathway (12).…”
Section: Introductionmentioning
confidence: 99%